Wilms' tumor 1 (WT1)-targeted cancer vaccines to extend survival for patients with pancreatic cancer. (November 2016) - Koido, Shigeo; Okamoto, Masato; Shimodaira, Shigetaka; Sugiyama, Haruo
Despite novel chemotherapy treatments, pancreatic ductal adenocarcinoma (PDA) remains a lethal disease. New targeted cancer vaccines may represent a viable option for patients with PDA. The Wilms' tumor 1 (WT1) antigen is one of the most widely expressed tumor-associated antigens in various types of tumors, including PDA. Recent reports have indicated that WT1-targeted cancer vaccines for patients with PDA mediated a potent antitumor effect when combined with chemotherapy in preclinical and clinical studies. This review summarizes the early-phase clinical trials of WT1-targeted cancer vaccines (peptide vaccines and dendritic cell-based vaccines) for PDA. Moreover, we will discuss future strategies for PDA treatments using WT1-specific cancer vaccines combined with immune checkpoint therapies to maximize the clinical effectiveness of PDA treatments.